2007
DOI: 10.2466/pr0.101.2.357-360
|View full text |Cite
|
Sign up to set email alerts
|

Measures of Expressions of Love

Abstract: This study developed scales for Chapman's five expressions of love: quality time, receiving gifts, words of affirmation, physical touch, and acts of service (two dimensions). A total of 338 student respondents were surveyed resulting in 321 usable surveys (95%). Of this total, 177 were women and 144 men, with a median age of 24 yr.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 3 publications
0
13
0
Order By: Relevance
“…This study was an effort to provide further empirical exploration of Chapman’s (2015a) LL model, which has been given only limited attention in the academic psychology literature despite its attractiveness to laypeople and its clinical utility. The intent behind this study was not so much to establish the validity of Chapman’s model (which was accomplished by Egbert & Polk, 2006; Goff et al, 2007; and Polk & Egbert, 2013). Instead, given that its process-oriented aspects are already well-established via comparable theory and research (as summarized and/or cited throughout this article), this study provided exploratory data pertaining not only to men’s and women’s primary LLs but also to the differences within the couple , quantified via Cohen’s d effect sizes, across the combination of all five LLs as they appeared in couples.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study was an effort to provide further empirical exploration of Chapman’s (2015a) LL model, which has been given only limited attention in the academic psychology literature despite its attractiveness to laypeople and its clinical utility. The intent behind this study was not so much to establish the validity of Chapman’s model (which was accomplished by Egbert & Polk, 2006; Goff et al, 2007; and Polk & Egbert, 2013). Instead, given that its process-oriented aspects are already well-established via comparable theory and research (as summarized and/or cited throughout this article), this study provided exploratory data pertaining not only to men’s and women’s primary LLs but also to the differences within the couple , quantified via Cohen’s d effect sizes, across the combination of all five LLs as they appeared in couples.…”
Section: Discussionmentioning
confidence: 99%
“…First, Egbert and Polk (2006) found that their measure of individual participants' preferences for expressing affection using the LLs had acceptable reliability, ranging from Cronbach's ␣ ϭ .77 to .85. Second, for Goff, Goddard, Pointer, and Jackson (2007), who explored individual participants' preferences for receiving affection, internal consistency and reliability were deemed excellent, ␣ ϭ .84 to .92. However, it is worth noting that, in their sample, Acts of Service was split into separate dimensions (domestic/indoor service and outdoor/ shop service) based on participants' responses coupled with socially constructed gender-based lines.…”
Section: Factor Structurementioning
confidence: 99%
See 1 more Smart Citation
“…Touch is a central part of human interactions and is used to communicate one’s thoughts and feelings (Hertenstein et al, 2006, 2009). Specifically, romantic touch is one of the five expressions of love (Goff et al, 2007). Touch and love have been defined as ‘indivisible’ (Montagu, 1971).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, a significant association was found between hearing the imagery script of their primary LL and person’s heart rate and skin conductance, although no significant increase was found in the respiration rate. In addition, good internal consistency and reliability was reported for the scale measurement of the preferred LL [ 33 ].…”
Section: Introductionmentioning
confidence: 99%